Evaluasi perencanaan dan penerapan model pembelajaran teaching factory di SMK: Systematic Literature Review (SLR) - Nurulia Lutfi Hapsari; Sohidin Sohidin (Universitas Negeri Surabaya, 2026)
Vocational education in Indonesian Vocational High Schools (SMK) plays a strategic role in preparing a competent workforce in the industry 5.0 era. However, a mismatch between graduates’ competencies and industry needs persists, reflected in the 9.01% unemployment rate among SMK graduates in 2024. The Teaching Factory (TEFA) model integrates learning with industrial production processes to enhance students’ technical, managerial, and soft skills. This study employs a Systematic Literature Review (SLR) of 30 journal articles published between 2019 and 2025, sourced from Google Scholar and Scopus, and analyzed using the CIPP model (Context, Input, Process, Product). The findings show that TEFA planning includes industry needs analysis and curriculum alignment but faces constraints such as limited facilities and teacher competencies. Its implementation improves student competence, motivation, and work readiness, although challenges remain, including weak industry collaboration, limited policy support, low student motivation, and suboptimal occupational safety standards. Strengthening school–industry partnerships, adaptive curricula, and continuous evaluation is essential to improve graduate competitiveness.